Obstacling Factors for Distribution of DAK Fisik in the Districts of East Lampung Districts, Central Lampung Distrists And Metro City, 2020 – 2021 - Royhul Akbar; Subandi Subandi (Gorontalo State University, 2022)
DAK Fisik is a source of funds provided by the Central Government to support Regional Government Development. In 2021 in 3 Sub Regional/Local Governments within the scope of the Metro KPPN payment area, there are still obstacles to the distribution of DAK Fisik where in the 3 Regions the average Realization and Absobsion for DAK Fisik is only 81.91% in 2020 and 92.93% of the available ceiling in 2021. The biggest obstacle in distribution in the period 2020 and 2021 is the COVID-19 pandemic condition which limits the space for the implementation of distribution activities and the procurement process for goods and services that are required to use e-procurement but the goods needed in the E-Procurement application are not yet available.